2015
DOI: 10.1007/s12325-015-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin in the Clinical Setting: 8-Year Experience with Gram-positive Bacterial Infections from the EU-CORESM Registry

Abstract: IntroductionThe aim of this study was to evaluate the clinical outcomes and safety of daptomycin therapy in patients with serious Gram-positive infections.MethodsPatients were enrolled in the European Cubicin® Outcomes Registry and Experience (EU-CORESM), a non-interventional, multicenter, observational registry. The real-world data were collected across 18 countries (Europe, Latin America, and Asia) for patients who had received at least one dose of daptomycin between January 2006 and April 2012. Two-year fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Increased use of first-line daptomycin treatment for suspected and confirmed resistant pathogens, such as MRSA, reflects increasing awareness of daptomycin use for resistant pathogens and the limitations of available treatment options [ 31 , 32 , 44 ]. This pooled analysis reinforces the data from the previously published real-world reports (CORE and EU-CORE) [ 33 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Increased use of first-line daptomycin treatment for suspected and confirmed resistant pathogens, such as MRSA, reflects increasing awareness of daptomycin use for resistant pathogens and the limitations of available treatment options [ 31 , 32 , 44 ]. This pooled analysis reinforces the data from the previously published real-world reports (CORE and EU-CORE) [ 33 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Rege et al have reported good tolerability and high clinical success rates with daptomycin when administered for >14 days, in a patient population from the USA [ 34 ]. Similarly, the results from an 8-year clinical experience with daptomycin showed favorable safety and effectiveness profiles with lower overall clinical failure rates in Europe, Latin America, and Asia [ 33 , 40 , 43 ]. These results complement the previously published data from randomized clinical trials [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased frequency of gram-positive infections and the rise in resistance to commonly used antibiotics have led to the need of novel antibiotic therapies, such as DAP, which has high antimicrobial penetration into biofilms with low bactericidal concentration [13]. According to the European Registry, DAP was effective and safe in patients with osteomyelitis or those with orthopedic device infections; it was also a valuable treatment option for the management of gram-positive infections [3,14]. However, in the treatment of PJIs by using DAP, there is no consensus whether the implant should be removed or not.…”
Section: Discussionmentioning
confidence: 99%